2022
DOI: 10.1021/acs.jcim.2c01164
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Structural Studies of Zinc Chloroquine Complexes

Abstract: Chloroquine (CQ) is a first-choice drug against malaria and autoimmune diseases. It has been co-administered with zinc against SARS-CoV-2 and soon dismissed because of safety issues. The structural features of Zn−CQ complexes and the effect of CQ on zinc distribution in cells are poorly known. In this study, state-of-the-art computations combined with experiments were leveraged to solve the structural determinants of zinc−CQ interactions in solution and the solid state. NMR, ESI-MS, and X-ray absorption and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The maximum excitation peak of the spectrum is at 340 nm, and the corresponding emission peak is 384 nm after the addition of CQP (Figure S7). CQP can combine with Zn 2+ or complex to form a luminescent substance through N atoms of the CQP moiety. , The results indicate that the prepared fluorescent probe has different fluorescence phenomena compared to CQP under different excitations.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The maximum excitation peak of the spectrum is at 340 nm, and the corresponding emission peak is 384 nm after the addition of CQP (Figure S7). CQP can combine with Zn 2+ or complex to form a luminescent substance through N atoms of the CQP moiety. , The results indicate that the prepared fluorescent probe has different fluorescence phenomena compared to CQP under different excitations.…”
Section: Resultsmentioning
confidence: 92%
“…Bat model and molecular formula of CQP are exhibited in Figure S15. It has been reported that CQP can combine with metal ions or metal-containing fragments to form complexes through unsubstituted N atoms. , In order to verify the interaction of CQP with zinc in ZIF-90 resulting in enhanced fluorescence, CQP is added to the ZIF-90 solution, which displays significant luminescence enhancement (Figure S16a). In addition, the fluorescence lifetime fitting curve (Figure S16b) demonstrates that the fluorescence lifetime of original sample 1 is shorter (4.22 μs) but that of the sample is longer after CQP added (10.30 μs), which is in good agreement with the enhancement of fluorescence intensity at 384 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Such a high free energy barrier for the permeation of charged molecular species has been reported for ionizable drug-like molecules from previous MD simulations. 25,26 Protonated (neutral) cinnamic acid, on the other hand, shows a broad energy minimum (about −15 or −3.4 kcal/mol) centered around 1.5 nm from the bilayer center that is lower than the free energy in water (Figure 5d), where the molecule packs against stearyl alcohols and the polar COOH group is close to the surface (configuration (i) in Figure 5d). Free energy profiles of several amphiphilic drug-like molecules across a phospholipid bilayer calculated using MD simulations also show a broad minimum located between 1 and 2 nm distance from the bilayer center.…”
Section: Calculation Of the Free Energy Profile Of A Smallmentioning
confidence: 99%
“…22−26 In particular, the effect of the protonation state on the permeability of drug-like molecules across lipid bilayers has been studied. 25,26 Conventionally, charged molecules could not permeate spontaneously through the hydrophobic interior of lipid bilayers due to a high free energy barrier, but MD simulations suggest that dynamic charge neutralization may occur before diffusing through the lipid-tail region, which significantly lowers the permeation free energy barrier. 25 MD simulations have also been used to compare penetration free energy barriers for drug-like molecules between the fluid-phase phospholipid bilayer and gel-phase ceramide-2 bilayer, where the gel-phase bilayer presented almost 3 times higher barriers for the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Many computational and structural studies have evidenced the significance of Zn(II) complexes and reported they show a variety of geometries and coordination numbers of chelating ligands characterized by different hapticities and donor atoms. [17][18][19][20] In addition, several Zn(II) complexes have been recognized for their biological activities, including anti-convulsant, 21 antidiabetic, 22 antiinflammatory, 23 anti-microbial, 24 anti-oxidant, 25 anti-proliferative/ anti-tumour, 26 anti-Alzheimer's disease, 27 and anti-COVID-19 agents. 28 Many of these agents are able to interact with DNA molecules, 29 indicating different effects, such as DNA cleavage 30 and DNA duplex cross-linking.…”
Section: Introductionmentioning
confidence: 99%